STABILITY OF ARSENOPYRITE AT TEMPERATURES BELOW 300°C - Tyukova E.E.; Voroshin S.V. (My University, 2004)
This work is aimed at the thermodynamic calculations of arsenopyrite stability in medium- and low-temperature regions based on mineral relationships observed in nature.